PEMELAJARAN TATA BAHASA BERBASIS TEKS SISWA KELAS V SEKOLAH DASAR DI KOTA MEDAN - Rehan Halilah Lubis; nfn Nurelide (Madah: Jurnal Bahasa dan Sastra, 2017)
This research tries to solve Indonesian grammar learning problems faced by the teacher caused of the material out of the handhouts. Besides that, the student problems in differing preposition di anf prefikx di based on text. The problems that dicussed in this research are how the model of learning grammar text based on the fifth grade students in Medan and how the learning outcomes. The qualitative and quantitative method is used during the learning activities anddirect observation until they get their final score. The research is located at two different schools in Kecamatan Medan Selayang dan Medan Johor with 60 (sixty) students for each schools. The grammar learning model based on the text of the fifth grade in Medan creates learning system focus on students. The students have to identify, classify and find the problem. They have to solve it by the guidance of teachers. Teachers become facilitators and motivators on the teaching learning activity. The average score based on the model is 77,75. The score is 77,75, it is under good category.